Preparation of Pb(Zr0.52Ti0.48)O-3 thin films on Pt/RuO2 double electrode by a new sol-gel route - Kim, SH; Choi, YS; Kim, CE; Oh, YJ (MATERIALS RESEARCH SOCIETY, 1997)
Pb(Zr0.52Ti0.48)O-3 (PZT) thin film on Pt/RuO2 double electrode was successfully prepared by using a new alkoxide-alkanolamine, sol-gel method. It was observed that the use of Pt/RuO2 double electrode reduced leakage current, resulting in a marked improvement in the leakage characteristics and more reliable capacitors. Typical P-E hysteresis behavior was observed even at low applied voltage of 5 V, manifesting greatly improved remanence and coercivity, Fatigue and breakdown characteristics, measured at 5 V, showed stable behavior, and no degradation in polarization was observed up to 10(11) cycles.